The application of knowledge communication system models to library information science education [soundrecording] Tefco Saracevic. - Saracevic, Tefco (Development Digest premier series, 1973)
Draws on Shannon and Weaver's model of the communication process, Norman Weiner's cybernetic model, and the Goffman epidemic model of communication. Suggests viewing a library as one example of a knowledge communication system. Derives a curriculum for librarianship and information science based on it.